Development of a No-Wash Assay for Mitochondrial Membrane Potential Using the Styryl Dye DASPEI - Jensen, K; Rekling, J (2010)
Mitochondrial dysfunction is a hallmark of several diseases and may also result from drugs with unwanted side effects on mitochondrial biochemistry. The mitochondrial membrane potential is a good indicator of mitochondrial function. Here, the authors have developed a no-wash mitochondrial membrane potential assay using 2-(4-(dimethylamino)styryl)-N-ethylpyridinium iodide (DASPEI), a rarely used mitochondrial potentiometric probe, in a 96-well format using a fluorescent plate reader. The assay was validated using 2 protonophores (CCCP, DNP), which are known uncouplers, and the neuroleptic thioridazine, which is a suspected mitochondrial toxicant. CCCP and DNP have short-term depolarizing effects, and thioridazine has long-term hyperpolarizing effects on the mitochondrial membrane potential of Chinese hamster ovary (CHO) cells. The assay also detected changes of the mitochondrial membrane potential in CHO cells exposed to cobalt (mimicking hypoxia) and in PC12 cells exposed to amyloid β, demonstrating that the assay can be used in cellular models of hypoxia and Alzheimer’s disease. The assay needs no washing steps, has a Z′ value >0.5, can be used on standard fluorometers, has good post liquid-handling stability, and thus is suitable for large-scale screening efforts. In summary, the DASPEI assay is simple and rapid and may be of use in toxicological testing, drug target discovery, and mechanistic models of diseases involving mitochondrial dysfunction.